MARINE MACROALGAE BIODIVERSITY OF UJUNG GENTENG COASTAL AREA, WEST JAVA, INDONESIA BASED ON MORPHOLOGICAL AND GENETIC MARKER 18S RRNA - Yessy
Macroalgae are photosynthetic organisms which are macrobenthic (large and attached) forms of marine algae. Macrolgae are widely used in the sectors of food, agriculture, cosmetics, and pharmaceuticals. Approximately 8.6% of the total marine biota in Indonesia are macroalgae, which occupy an area of about 1.2 million hectares of ocean or the largest in the world. Ujung Genteng coastal area has high biodiversity because it is a relatively unspoiled coastal area with a wide intertidal zone and consists of a variety of habitats. Several studies on macroalgal diversity have been conducted in the Ujung Genteng coastal area. All of these diversity studies still use classical methods: morphological analysis. Morphological identification of species is often inaccurate due to morphological similarities, leading to loss of information regarding species composition in an ecosystem or in an area. The molecular method approach using genetic markers is very useful in studying species, especially macroalgae and can answer questions about the relationship between taxa (taxa) and populations and divergence. Molecular methods can overcome deficiencies in morphological studies used previously. DNA sequence information enables the identification of species that were previously ambiguous and hidden in an environment. The 18S rRNA gene sequence can be used as a genetic marker for the identification of macroalgae species because it has conserved and variable regions that are useful in species determination. This study aims to examine the diversity of macroalgae in Ujung Genteng coastal area, West Java, Indonesia based on morphology and genetics with the 18S rRNA marker gene. The assessment was carried out at two locations on Ujung Genteng Beach, namely Location 1 which is categorized as an unpolluted beach because due to the lack of human, domestic, transportation and industrial activity, and Location 2 which is categorized as a polluted coastal area because there are human, domestic, transport or industrial activities take place around it. The research methodology included: (i) macroalgae sampling in the Ujung Genteng coastal area, West Java; (ii) measurement of seawater conditions for macroalgae habitat including measurements of pH, temperature, salinity, and metal content; (iii) morphological analysis of macroalgae samples; (iv) total DNA isolation from macroalgae samples; (v) amplification of the 18S rRNA gene using the PCR method (vi) determination of